2004
DOI: 10.1159/000082032
|View full text |Cite
|
Sign up to set email alerts
|

Clinical-Biochemical Correlations in Acromegaly at Diagnosis and the Real Prevalence of Biochemically Discordant Disease

Abstract: Objective: To analyze clinical-biochemical correlations in newly diagnosed acromegaly, focusing in particular on patients with discrepant parameters. Design: Retrospective study. Methods: Data from 164 patients with acromegaly seen between 1995 and 2003. Patients were reviewed for the presence of headaches, arthralgias, hypertension, menstrual abnormalities, impotence, glucose intolerance or diabetes. Biochemical evaluation consisted of age- and gender-adjusted IGF-I levels and glucose-suppressed GH. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
3
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 49 publications
4
36
3
1
Order By: Relevance
“…On the basis of the present results (3/2,270), the number of cases of acromegaly is 264 in 200,000 adults with DM or GI. Considering that DM or GI occurs in 55% of patients with acromegaly [13][14][15][16][17][18][19], there would be 216 additional cases among the 800,000 adults without DM or GI, corresponding to 480 cases/1,000,000 adults (90% CI: 136-1,280).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the present results (3/2,270), the number of cases of acromegaly is 264 in 200,000 adults with DM or GI. Considering that DM or GI occurs in 55% of patients with acromegaly [13][14][15][16][17][18][19], there would be 216 additional cases among the 800,000 adults without DM or GI, corresponding to 480 cases/1,000,000 adults (90% CI: 136-1,280).…”
Section: Resultsmentioning
confidence: 99%
“…Diabetes mellitus (DM) or glucose intolerance (GI) are observed in about 55% of patients with acromegaly [13][14][15][16][17][18][19], a rate much higher than that found in the general adult population [approximately 15-20% in the Brazilian population [20][21][22]. This difference makes these conditions attractives for the investigation of the presence of acromegaly and to estimate the prevalence of the disease in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Enlargement of the extremities is an early and almost universal manifestation of acromegaly (23)(24)(25)(26)(27)(28)(29). In fact, a previous study suggested that the presence of this finding evaluated by two simple questions is an objective, simple and cost-effective method to define a "suspicious phenotype" (3).…”
Section: Discussionmentioning
confidence: 99%
“…However, we believe that the disease is unlikely in the four patients of our series with this finding considering the presence of only slightly elevated serum IGF-1 and nadir GH and the absence of a tumor on MRI. In fact, cases of acromegaly with GH suppression in the OGTT exhibited apparent adenoma on MRI (27)(28)(29)(30)(31)(32). Furthermore, ectopic production of GHRH is unlikely in the presence of the biochemical findings cited, normal MRI (no hyperplasia), and absence of a tumor on chest and abdominal CT scans (33).…”
Section: Discussionmentioning
confidence: 99%
“…With increasing frequency, multidisciplinary groups from these centers publish their experience in the diagnosis and management of acromegaly. Several important Latin American publications have appeared in the medical literature, covering the oncogenesis of somatotrophinomas [14, 15], the clinical aspects of acromegaly [16] and its complications [17, 18], as well as the results of the surgical [19, 20], pharmacological [2124] and radiotherapeutical management of the disease [25]. Interestingly, the outcomes of transsphenoidal surgery, radiotherapy and therapy with somatostatin analogs described in these publications are comparable to those reached in academic institutions from Europe and the United States [1925].…”
mentioning
confidence: 99%